A Case Report on Care-Seeking Type Illness Anxiety Disorder after COVID-19 Infection - Kasi, Lakshmi S.; Moorthy, Bini (Case Reports in Psychiatry, 2023)
This case report highlights the diagnostic challenges presented by the overlapping symptoms of illness anxiety disorder (IAD) and long COVID-19 (LC-19). This case report focuses on a 58-year-old woman with care-seeking type IAD in the context of LC-19-associated symptoms. The patient experienced mild COVID-19 in August 2021. Since then, she has reported an increase in LC-19-associated symptoms, including cognitive deficits, breathlessness, fatigue, and anosmia. Despite largely normal laboratory results, imaging, and physical examinations, the patient’s distress and care-seeking behaviors persisted, resulting in the diagnosis of IAD. Accurately differentiating between LC-19 and IAD is crucial for appropriate patient care. We discuss the importance of recognizing and treating IAD in patients with LC-19-associated symptoms and the need for further research on the correlation between IAD and both COVID-19 and LC-19.